Evaluation of IFN-gamma and TNF-alpha as immunological markers of clinical outcome in cutaneous leishmaniasis - Argemiro D'Oliveira Junior; Paulo Machado; Olívia Bacellar; Lay Har Cheng; Roque P. Almeida; Edgar M. Carvalho (Revista da Sociedade Brasileira de Medicina Tropical, 2002)
To evaluate if IFN-gamma and TNF-alpha levels could be used as markers of therapeutic response in cutaneous leishmaniasis, 54 patients with history of one ulcerated cutaneous lesion, with up to 30 days onset, were enrolled in the study. IFN-gammaand TNF-alpha were measured by ELISA in lymphocyte cultures supernatant before and 60 days after initiating therapy. Cure was considered to be a complete healing of lesion 60 days after treatment. IFN-gamma and TNF-alpha levels were similar in both groups of patients before therapy. There was a tendency to increase IFN-gamma levels in patients that were cured in 60 days, however the values did not reach statistical significance. In both groups of patients, TNF-alpha levels were similar before therapy and fell significantly after treatment, irrespective of cure or maintenance of active lesion.